DMT for Load-Settlement Curve Prediction in a Tropical Sandy Soil Compared to Plate Load Tests - Dos Santos, Roberto A. [UNESP]; Rocha, Breno P.; Giacheti, Heraldo L. [UNESP] (Amer Soc Testing Materials, 2020)
The flat dilatometer test (DMT) has been used as an accurate in situ site investigation tool for foundation settlement prediction. However, few investigations have assessed its performance in settlement prediction in unusual soils. In addition, very little work has been performed to obtain a complete load-settlement prediction curve. This article assesses an approach that uses the DMT to obtain a complete load-settlement prediction curve at a tropical sandy soil site under both natural and inundated conditions. DMTs, plate load tests, and oedometer tests were carried out in these two moisture conditions at the experimental research site located in Bauru, Sao Paulo State, Brazil. The obtained data showed good agreement between the load-settlement curve predicted by the DMT and those determined by the plate load tests at four different depths and two soil conditions. The presented interpretation method based on DMT data worked well to predict the complete load-settlement curve at an unusual soil site at different depths and soil moisture content conditions.
Keywords: in situ testing; flat dilatometer test; shallow foundation; load-settlement curve; settlement